Tales from India - Gray, J. E. B.; Fowler, Rosamund (Oxford University Press Oxford, 2001)
"Beautifully told retellings of classic stories from India. Full of richness and warmth, these tales of tender love, great heroism, acts of sacrifice, foolishness and friendship come vividly to life. There is an epic battle in which monkeys and bears help rescue the beautiful princess Sita from evil demons and a simple fable about a jackal who tries to become king. This tapestry of stories is as colourful and diverse as India itself. Sources in selecting the stories have been Sanskrit and Pali, the classical languages of the Brahmans and the Buddhists. Many of these tales were current centuries before the Christian era and were given a sophisticated form by the storytellers of classical times." Publisher description